Effect of asam kandis (Garcinia cowa Roxb) extract in drinking water on egg quality of Japanese quail (Coturnix coturnix japonica) - Arif Darmawan; Widya Hermana; Muhamad Prastyo Dirgantara (Aceh Journal of Animal Science, 2021)
Asam kandis  (Garcinia  cowa  Roxb)  fruit has been reported to contain phytochemicals such as xanthon, hydroxy cytric acid and flavonoids that have various activities such as antimicrobial and antioxidant. This study was aimed  to investigate the effect of asam kandis extract addition in drinking water on the quality of quail eggs. Ninety nine laying quails of 59  days of age were divided into 3 treatments and 3 replications with 11 laying quails in each replication. Completely Randomized Design was used and the treatments were: T1= control  (drinking water without asam  kandis extract), T2= drinking water with asam kandis extract at pH 4, T3= drinking water with asam kandis extract at pH 3. The parameters observed were egg weight, egg shape index, yolk color, yolk percentage, albumen percentage, eggshell percentage,  shell thickness, and haugh unit score. The data obtained were analyzed by Analysis of Variance (ANOVA) and significant  differences among treatments means were tested  by Duncans multiple test. The  the addition of asam kandis extract did not affect (P0.05) on egg weight, egg shape index, yolk color, yolk percentage, albumen percentage, eggshell percentage, and haugh unit score. The addition of asam kandis extract in drinking water at pH 3 significantly (P0.05) increased eggshell thickness compare to that of other treatments. The conclusion was the addition of asam kandis extract in drinking water at pH 3 increased eggshell thickness without decreasing egg quality.